Gendered Citizenship: A Case Study Of Paid Filipino Male Live-in Caregivers In Toronto - Nyaga, Dionisio; Torres, Rose Ann (Penerbit Universiti Sains Malaysia (USM Press), 2017)
Philippines is considered as a major provider of caregiving services in Canada. Caregiving has historically been identified as feminine labour. As such, providing paid caregiving has always been associated with immigrant women. Policies are thus built to control this work and mostly they tie with the masculine culture of the society. In Canada, live-in caregiving is very gendered and masculine, and as such it discriminated men of colour. This paper is focused on a case study that was done in 2014 in Toronto. There were three paid Filipino male live-in caregivers who participated in this study. The study applied qualitative narrative research methodology.